Impact of PBP2a Assay on Antibiotic Therapy of Patients with Non-Blood, Non-Urine Staphylococcus aureus Infections. (4th October 2017) - Shulder, Stephanie; Adams-Sommer, Victoria; Cosgrove, Sara E; Dzintars, Kathryn; Simner, Patricia; Tamma, Pranita D; Avdic, Edina
Abstract: Background: Rapid diagnostic tests can reduce time to organism identification and susceptibility results, allowing for more rapid optimization of antibiotic therapy. We sought to determine whether a qualitative immunochromatographic assay (Alere™ PBP2a Culture Colony test) that differentiates methicillin-susceptible S. aureus (MSSA) from methicillin-resistant S. aureus (MRSA) could optimize time to appropriate therapy for patients with skin and soft-tissue infections (SSTIs) and nosocomial pneumonia caused by S. aureus . Methods: Adult patients admitted to The Johns Hopkins Hospital with a respiratory or wound culture growing S. aureus between July-October 2015 (baseline period) and July-October 2016 (intervention period) were included. The primary outcome was time to optimal antibiotic therapy from specimen collection before and after implementation of the PBP2a assay. Secondary outcomes were (1) time to antibiotic de-escalation from specimen collection, (2) length of hospital stay, and (3) number of vancomycin levels. An unadjusted analysis was conducted using Chi-square or Fisher's exact test for categorical variables and Wilcoxon rank-sum test for continuous variables. Results: 189 patients met eligibility criteria (119 baseline, 70 intervention). There were no significant differences in characteristics of patients between periods. Overall time to optimal therapy decreased during the intervention period compared with baseline (IQR 0–24.7 hours vs. 0–64.2 hours, P = 0.02). In the subset of patients with SSTIs, time to optimal and de-escalation of antibiotic therapy was reduced during the intervention period compared with baseline (IQR 0–6.6 vs. 0-70.8, P = 0.02 and IQR 0–26.5 vs. 0-65.5, P = 0.05, respectively), but not with pneumonia. Length of hospital stay (median 6 days in each, P = 0.60) and number of vancomycin levels (median 0 vs. 1, P = 0.33) were similar before and after assay implementation. Conclusion: There was a reduction in time to optimal antibiotic therapy after implementation of the PBP2a assay driven by changes in SSTI regimens but not pneumonia regimens. Incorporation of a rapid test to differentiate MSSA from MRSA be a useful addition to antibiotic stewardship initiatives to optimize therapy for patients with MSSA infection. Disclosures: P. Simner, bioMerieux: Research Contractor, Research support Check-Points Health BV: Research Contractor, Research support